The Potential Role of Everlasting Flower (Helichrysum stoechas Moench) as an Antihypertensive Agent: Vasorelaxant Effects in the Rat Aorta - Marta Sofía Valero; Sonia Nuñez; Francisco Les; Marta Castro; Carlota Gómez-Rincón; María Pilar Arruebo; Miguel Ángel Plaza; Ralf Köhler; Víctor López (MDPI AG, 2022)
Helichrysum stoechas (L.) Moench (H. stoechas) is a medicinal plant traditionally used in the Iberian Peninsula to treat different disorders such as arterial hypertension. The aim of this study was to investigate the vascular effects of a polyphenolic methanolic extract of H. stoechas, which has high antioxidant activity, and its mechanism of action. Isometric myography studies were performed in an organ bath with rat aortic rings with intact endothelium. The H. stoechas extract produced vasorelaxation in the aortic rings that were precontracted by phenylephrine or KCl. L-NAME and Rp-8-Br-PET-cGMPS but not indomethacin or H-89; it also reduced the relaxant response evoked by H. stoechas extract on the phenylephrine-induced contractions. H. stoechas extract reduced the response to CaCl2 similar to verapamil and reduced the phenylephrine-induced contractions comparable with heparin. TRAM-34, apamin and glibenclamide reduced relaxation induced by the H. stoechas extract. The combination of L-NAME+TRAM-34+apamin almost completely inhibited the H. stoechas-induced effect. In conclusion, the relaxant effect of the H. stoechas extract is partially mediated by endothelium through the activation of the NO/PKG/cGMP pathway and the opening of Ca2+-activated K+ channels. Furthermore, the decrease in the cytosolic Ca2+ by the inhibition of Ca2+ influx through the L-type Ca2+ channels and by the reduction of Ca2+ release from the sarcoplasmic reticulum via the IP3 pathway is also involved.